2022
DOI: 10.3390/jcm11102813
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Glycemic Variability and Hypoglycemic Events in Hospitalized Older Adults Treated with Basal Insulin plus Vildagliptin and Basal–Bolus Insulin Regimen: A Prospective Randomized Study

Abstract: Background: The basal–bolus insulin regimen is recommended in hospitalized patients with diabetes mellitus (DM), but has an increased risk of hypoglycemia. We aimed to compare dipeptidyl peptidase 4 inhibitors (DPP4-i) and basal–bolus insulin glycemic outcomes in hospitalized type 2 DM patients. Methods and patients: Our prospective randomized study included 102 elderly T2DM patients (82 ± 9 years, HbA1c 6.6% ± 1.9). Glycemic control: A variability coefficient assessed by continuous glucose monitoring (Free St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…For example, in a 6 month open-label RCT comparing a DPP-4i (linagliptin) with basal insulin (glargine) in long-term care and skilled nursing facilities, mean daily blood glucose was similar, with fewer hypoglycaemic events with linagliptin compared with insulin [ 181 ]. Treatment of inpatient hyperglycaemia with basal insulin plus DPP-4i has been demonstrated to be effective and safe in older adults with type 2 diabetes, with similar mean daily blood glucose but lower glycaemic variability and fewer hypoglycaemic episodes compared with the basal–bolus insulin regimen [ 182 ].…”
Section: Therapeutic Options: Lifestyle and Healthy Behaviour Weight ...mentioning
confidence: 99%
“…For example, in a 6 month open-label RCT comparing a DPP-4i (linagliptin) with basal insulin (glargine) in long-term care and skilled nursing facilities, mean daily blood glucose was similar, with fewer hypoglycaemic events with linagliptin compared with insulin [ 181 ]. Treatment of inpatient hyperglycaemia with basal insulin plus DPP-4i has been demonstrated to be effective and safe in older adults with type 2 diabetes, with similar mean daily blood glucose but lower glycaemic variability and fewer hypoglycaemic episodes compared with the basal–bolus insulin regimen [ 182 ].…”
Section: Therapeutic Options: Lifestyle and Healthy Behaviour Weight ...mentioning
confidence: 99%
“…Due to their high tolerability and modest efficacy, DPP4i may be suitable for specific populations. For instance, inpatient treatment of hyperglycaemia with basal insulin plus DPP4i has proven to be effective and safe in older adult patients with T2D, yielding similar glycaemic levels but with less glycaemic variability and fewer hypoglycaemic episodes compared with basal-bolus insulin regimens 37 .…”
Section: Dipeptidyl Peptidase-4 Inhibitorsmentioning
confidence: 99%
“…However, these studies showed inconclusive results regarding the influence of glycemic control prior to admission on the appearance of hypoglycemia [ 6 , 7 ]. Few studies have addressed the influence of antidiabetic drugs that are unlikely to produce hypoglycemia [ 11 ].…”
Section: Introductionmentioning
confidence: 99%